DETERMINATION OF DEPTH OF PLACEMENT OF TUNNELS AND CAVITIES BY THE BOUNDARY ELEMENT METHOD (Journal of Engineering, 2006)
A boundary element numerical algorithm has been developed for the determination of stresses anddeformations around cavities and tunnels. A study of the influence of depth below the groundsurface on the distribution of stresses and deformations around cavities and tunnels is presented inthis paper. The soil is assumed to behave linearly elastic.A computer program has been built to perform the numerical computations. The results show thatwith increasing the depth of placement of tunnel or opening below the ground surface, the settlements decrease. The maximum stresses occur at the haunches of the tunnel rather than at the crown. For the circular cavity that is considered in this paper, it was found that with increasing the depth below the ground surface (depth/tunnel diameter > 3), the surface settlements do not exceed 6 % from those obtained for the case of no-cavity condition.